Zionist architecture of the first two decades of the 20th century: From Orientalism to Occidentalism - Vladimir Ruzhansky (Urbis et Orbis: Mikroistoriâ i Semiotika Goroda, 2021)
This article is devoted to the history of Zionist Orientalism in Tel Aviv architecture. For a long time, this topic was a kind of taboo in Zionist historiography due to political reasons caused by the Arab-Israeli conflict. For this reason, Zionist Orientalism is still one of the least studied topics in the history of modern Israel. Meanwhile, this trend, albeit for a short period of time, was dominant in Zionism at the beginning of the 20th century. The most famous representative of this trend was the philosopher and theologian Martin Buber. In architecture, Zionist Orientalism was embodied in a special style known as “Eretz Israel”. This style combined the Arab tradition, the Moorish or pseudo-Eastern direction in European architecture of the 19th century, and the ideas of Zionist architects about how the First Temple should have looked. It is important to emphasize that this architectural style was a kind of Zionist manifesto, proclaiming a break with anti-Semitic Europe and at the same time the readiness of Jews to integrate into the Arab East. However, the permanent Arab-Israeli conflict, which originated with the Jewish pogroms in Palestine in 1920, completely changed the outlook and sentiments of the Zionist pioneers. In addition, the romantics from the First and Second Aliyahs in the third decade of the 20th century were replaced by pragmatists – representatives of the middle class from Eastern Europe, for whom the utilitarian component of the city under construction was much more important than the ideological one. As a result, “Eretz Israel” gave way to a new style – the utilitarian, European “Bauhaus”. The article details the dramatic history of architectural changes that took place in the young city over the course of one decade – from 1909, when Tel Aviv was founded, to 1920, when the conflict between Jews and Arabs turned into a stage of bloody confrontation. The article also analyzes the factors that determined the fate of not only the architectural style “Eretz Israel”, but also the further development of the first Hebrew city in Eretz Israel. To solve these problems, research methods such as comparative historical and historical psychological analysis are used. The central place in this article belongs to the history of the two main streets from which Tel Aviv began, namely, Rothschild Boulevard and Herzliya Gymnasium. The first set is the vector for the development of the city. As for the Herzliya gymnasium, which symbolized Zionist Orientalism, its history ended in the early sixties of the last century, when the building was completely destroyed. The destruction of the gymnasium building and the construction of a high-rise building in its place was also symbolic – Israel finally abandoned Orientalism and the Zionist romance inextricably linked with it and took a decisive course towards the West. The architecture of today‘s Tel Aviv is the result of the development and struggle of these two trends.